Preparation method of light composite porcelain clay

Through the combination of modified silicon carbide whiskers, silicone resin and montmorillonite and gradient heating sintering technology, the unutilized problem of ceramic potential in the application of energy-saving wall materials in the existing technology is solved, and the efficient insulation of lightweight composite porcelain clay is achieved and crack resistance is improved.

CN119263774AActive Publication Date: 2025-01-07广东枫树陶瓷原料有限公司
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411604257.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-07
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

It is difficult to develop new energy-saving wall materials with the advantages of lightweight, high strength, thermal insulation, fire and earthquake resistance, etc. The application of ceramics in this field has not yet fully utilized its potential.

Method used

By modifying materials such as silicon carbide whiskers, silicon resin and montmorillonite, and using gradient heating sintering technology, lightweight composite porcelain clay with excellent thermal insulation and crack resistance is formed.

Benefits of technology

It improves the plasticity and thermal insulation of lightweight composite porcelain clay, reduces thermal conductivity, enhances crack resistance, and meets the energy-saving and thermal insulation needs of buildings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005129113330000021
    Figure BDA0005129113330000021
  • Figure BDA0005129113330000031
    Figure BDA0005129113330000031
  • Figure BDA0005129113330000032
    Figure BDA0005129113330000032
Patent Text Reader

Abstract

The invention discloses a preparation method of light composite porcelain clay, and relates to the field of ceramics. When the light composite porcelain clay is prepared, dopamine is polymerized on the surfaces of silicon carbide whiskers to obtain modified silicon carbide whiskers; the preparation method comprises the following steps: reacting 3-glycidyl propyl (dimethoxy) methylsilane, methyltriethoxysilane, dimethyl diethoxysilane and methyldiethoxysilane, and then grafting 2-propylene-1-boric acid to obtain modified silicon resin; the preparation method comprises the following steps: uniformly mixing montmorillonite, polyethylene glycol, styrene, 4-vinyl aniline and divinyl benzene to obtain modified montmorillonite; and uniformly mixing the modified montmorillonite, the modified silicon resin and the composite ceramic powder, and carrying out gradient heating sintering to obtain the lightweight composite porcelain clay. The light composite porcelain clay prepared by the invention has excellent plasticity, heat retaining property and crack resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramics, and in particular to a method for preparing light composite porcelain clay. Background Art

[0002] In recent years, with the continuous rise of the wave of new wall material reform, people have a strong awareness of thermal insulation and energy saving in buildings, and the requirements for human living experience are getting higher and higher. The development of new energy-saving wall materials with the advantages of light weight, high strength, thermal insulation, fire resistance and earthquake resistance has been greatly favored by people. Ceramics have broad prospects in the field of innovation of new wall materials and development of new building energy-saving materials. It is expected to replace cement and stone to become the light and coarse aggregate of cast-in-place aggregates of assembled concrete such as reinforced concrete shear walls, beams, columns, and floor slabs. This reduces the weight of the building itself and can also improve the ability of thermal insulation, heat insulation, sound absorption and noise reduction in the indoor space of the building. Therefore, the present invention prepares a lightweight composite porcelain clay with excellent thermal insulation. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing a lightweight composite porcelain clay to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0005] A method for preparing a lightweight composite porcelain clay comprises the following steps:

[0006] (1) mixing silicon carbide whiskers and 0.02-0.03 mol / L tris(hydroxymethyl)aminomethane) aqueous solution at a mass ratio of 1:(1500-2500), ultrasonically dispersing for 20-30 min, adding 1-3 g / L dopamine hydrochloride, stirring at 20-30° C. and 200-300 rpm for 15-17 h, filtering, washing with deionized water for 3-5 times, and drying at 60-70° C. for 8-10 h to obtain modified silicon carbide whiskers;

[0007] (2) 3-glycidylpropyl(dimethoxy)methylsilane, methyltriethoxysilane, dimethyldiethoxysilane, methyldiethoxysilane and tetrahydrofuran were mixed and stirred at 25-35°C and 200-300 rpm for 20-30 min, and a hydrochloric acid solution of 5-6 times the mass of 3-glycidylpropyl(dimethoxy)methylsilane was added at a uniform rate within 6-8 min, and the stirring was continued for 23-25 ​​h. The temperature was raised to 50-60°C and the stirring was continued for 23-25 ​​h. The mixture was rotary evaporated for 1-2 h, and ethyl acetate was added for extraction. Wash with saturated sodium hydroxide solution for 3 to 5 times, dry with anhydrous calcium chloride for 23 to 25 hours to obtain silicone resin; mix silicone resin, 2-propylene-1-boric acid, chloroplatinic acid and toluene in a mass ratio of 1: (1 to 2): (0.01 to 0.03): (4 to 6), stir at 65 to 75° C. and 100 to 200 rpm for 10 to 20 minutes in a nitrogen atmosphere, heat to 105 to 115° C. and continue stirring for 11 to 13 hours, rotary evaporate at 65 to 75° C. for 1 to 2 hours, and naturally cool to room temperature to obtain modified silicone resin;

[0008] (3) Mix montmorillonite, polyethylene glycol and deionized water in a mass ratio of 1:(0.06-0.07):(60-70), perform ultrasonic dispersion at 20-30°C for 5-15 min, heat to 80-90°C, add styrene (2.2-2.4 times the mass of montmorillonite), 4-vinylaniline (0.5-1.5 times the mass of montmorillonite), dibenzoyl peroxide (0.06-0.07 times the mass of montmorillonite) and divinylbenzene (0.3-0.5 times the mass of montmorillonite), stir for 1-2 h, heat to 90-100°C and continue stirring for 0.9-1.1 h, cool naturally to room temperature, filter, wash with deionized water 3-5 times, and dry at 55-65°C for 23-25 ​​h to obtain modified montmorillonite;

[0009] (4) The modified montmorillonite, modified silicone resin and ethanol solution are mixed in a mass ratio of 1: (0.1-0.2): (0.2-0.3), and ultrasonically dispersed for 1-2 hours, and 0.05-0.06 times the mass of the modified montmorillonite modified silicon carbide whiskers are added, and stirred at 900-1100 rpm for 11-13 hours, and 0.1-0.2 times the mass of the modified montmorillonite composite ceramic powder is added, and granulated by a disc granulator at 45-55 r / min, and dried at 80-90°C for 11-13 hours to obtain a green body; the green body is gradually heated and then naturally cooled to room temperature to obtain a lightweight composite porcelain clay.

[0010] As an optimization, the silicon carbide whiskers in step (1) come from Qinghe County Chaotai Metal Materials Co., Ltd.

[0011] As an optimization, the reaction equation for modifying the silicon carbide whisker in step (1) is:

[0012]

[0013] As an optimization, in step (2), 3-glycidylpropyl(dimethoxy)methylsilane, methyltriethoxysilane, dimethyldiethoxysilane, methyldiethoxysilane and tetrahydrofuran are mixed in a mass ratio of 1:2:0.7:0.8:19.

[0014] As an optimization, the pH of the hydrochloric acid solution in step (2) is 1.

[0015] As an optimization, the reaction equation of the silicone resin in step (2) is:

[0016]

[0017] As an optimization, the reaction equation of the modified silicone resin in step (2) is:

[0018]

[0019] As an optimization, the polyethylene glycol model in step (3) is PEG-400E, which is from Shanghai Tichem Industrial Co., Ltd.

[0020] As an optimization, the volume fraction of the ethanol solution in step (4) is 50%.

[0021] As an optimization, the composite ceramic powder in step (4) is obtained by mixing potassium feldspar powder and white gangue powder in a mass ratio of 1:0.3, and milling with corundum balls on a planetary ball mill for 4 hours.

[0022] As an optimization, the gradient temperature increase in step (4) is to increase the temperature to 400°C at a rate of 5°C / min, preheat for 60 minutes, increase the temperature to 1000°C at a rate of 4°C / min, keep it for 2 hours, and then increase the temperature to 1450°C at a rate of 2°C / min, and keep it for 4 hours.

[0023] As an optimization, the composite ceramic powder in step (4) is obtained by mixing potassium feldspar powder and white gangue powder.

[0024] As an optimization, the potassium feldspar powder model is 325 mesh and comes from Shuangshi Mineral Products Processing Plant in Lingshou County.

[0025] As an optimization, the white gangue powder model is 325 mesh and comes from Lingshou County Zhanxing Mineral Products Co., Ltd.

[0026] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0027] When preparing light composite porcelain clay, the present invention comprises the following steps: polymerizing dopamine on the surface of silicon carbide whiskers to obtain modified silicon carbide whiskers; reacting 3-glycidylpropyl (dimethoxy)methylsilane, methyltriethoxysilane, dimethyldiethoxysilane and methyldiethoxysilane, and grafting 2-propylene-1-boric acid to obtain modified silicone resin; mixing montmorillonite, polyethylene glycol, styrene, 4-vinylaniline and divinylbenzene to obtain modified montmorillonite; and mixing the modified montmorillonite, modified silicone resin and composite ceramic powder, and then sintering them at a gradient temperature to obtain light composite porcelain clay.

[0028] Firstly, dopamine is polymerized on the surface of silicon carbide whiskers to obtain modified silicon carbide whiskers; 3-glycidylpropyl(dimethoxy)methylsilane, methyltriethoxysilane, dimethyldiethoxysilane and methyldiethoxysilane are reacted and then grafted with 2-propylene-1-boric acid to obtain modified silicone resin; a layer of polydopamine is formed on the surface of silicon carbide whiskers, and phenolic hydroxyl groups can not only form reversible crosslinks with boric acid, but also form covalent crosslinks with amino groups and coordinate bonds with metals, thereby improving the plasticity of lightweight composite porcelain clay; carbonization of polydopamine during sintering can also generate pores, thereby improving the thermal insulation of lightweight composite porcelain clay; 2-propylene-1-boric acid is grafted by hydrosilylation to introduce a boric acid structure, thereby forming a reversible borate ester crosslinking network at low temperature, and undergoing a carbon thermal reduction reaction with free carbon during high-temperature calcination to fill and support the pore structure, thereby improving the plasticity and crack resistance of lightweight composite porcelain clay.

[0029] Secondly, montmorillonite, polyethylene glycol, styrene, 4-vinylaniline and divinylbenzene are mixed to obtain modified montmorillonite; the modified montmorillonite, modified silicone resin and composite ceramic powder are mixed and then sintered at a gradient temperature to obtain a lightweight composite porcelain clay; polyethylene glycol and styrene are used to synergistically form pores during high-temperature calcination to improve the thermal insulation of the lightweight composite porcelain clay; at the same time, 4-vinylaniline participating in surface polymerization introduces an amino group, which reacts with the epoxy group in the silicone resin at a low temperature to form a chemically bonded and high-temperature removable hydroxyl group. The base structure can further improve the plasticity and thermal insulation of the lightweight composite porcelain clay; the modified silicone resin can reduce the thermal conductivity of the ceramic, form pores during high-temperature sintering, reduce the ceramic density, and improve the thermal insulation of the lightweight composite porcelain clay; the gradient temperature rise calcination is used to ensure that the organic matter is fully oxidized at 400°C to form pores, the montmorillonite undergoes a phase change at 1000°C, changes the microstructure, and inhibits the propagation and expansion of cracks, and boron undergoes a carbon thermal reduction reaction with free carbon at 1400°C, thereby improving the thermal insulation and crack resistance of the lightweight composite porcelain clay. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0031] Embodiment 1:

[0032] A method for preparing a lightweight composite porcelain clay, the method comprising the following preparation steps:

[0033] (1) Silicon carbide whiskers and 0.02 mol / L tris(hydroxymethyl)aminomethane) aqueous solution were mixed at a mass ratio of 1:1500, ultrasonically dispersed for 20 min, 1 g / L dopamine hydrochloride was added, stirred at 20° C. and 200 rpm for 17 h, filtered, washed with deionized water for 3 times, and dried at 60° C. for 10 h to obtain modified silicon carbide whiskers;

[0034] (2) 3-glycidylpropyl(dimethoxy)methylsilane, methyltriethoxysilane, dimethyldiethoxysilane, methyldiethoxysilane and tetrahydrofuran were mixed, stirred at 25°C and 200 rpm for 30 min, and a hydrochloric acid solution 5 times the mass of 3-glycidylpropyl(dimethoxy)methylsilane was added at a uniform rate within 6 min, and the stirring was continued for 25 h. The mixture was heated to 50°C and stirred for 25 h. The mixture was rotary evaporated for 1 h. Ethyl acetate was added for extraction. The mixture was washed with saturated sodium hydroxide solution for 3 times and dried with anhydrous calcium chloride for 23 h to obtain a silicone resin. The silicone resin, 2-propylene-1-boric acid, chloroplatinic acid and toluene were mixed in a mass ratio of 1:1:0.01:4, stirred at 65°C and 100 rpm in a nitrogen atmosphere for 20 min, heated to 105°C and stirred for 13 h. The mixture was rotary evaporated at 65°C for 2 h and naturally cooled to room temperature to obtain a modified silicone resin.

[0035] (3) Mix montmorillonite, polyethylene glycol and deionized water in a mass ratio of 1:0.06:60, ultrasonically disperse at 20°C for 5 minutes, heat to 80°C, add styrene (2.2 times the mass of montmorillonite), 4-vinylaniline (0.5 times the mass of montmorillonite), dibenzoyl peroxide (0.06 times the mass of montmorillonite) and divinylbenzene (0.3 times the mass of montmorillonite), stir for 2 hours, heat to 90°C and continue stirring for 1.1 hours, cool naturally to room temperature, filter, wash with deionized water three times, and dry at 55°C for 25 hours to obtain modified montmorillonite;

[0036] (4) The modified montmorillonite, modified silicone resin and ethanol solution were mixed in a mass ratio of 1:0.1:0.2, ultrasonically dispersed for 1 hour, 0.05 times the mass of modified silicon carbide whiskers of the modified montmorillonite were added, stirred at 900 rpm for 13 hours, and 0.1 times the mass of composite ceramic powder of the modified montmorillonite were added. The mixture was stirred and granulated with a disc granulator at 45 r / min, and dried at 80°C for 13 hours to obtain a green body; the green body was gradually heated and then naturally cooled to room temperature to obtain a lightweight composite porcelain clay.

[0037] Embodiment 2:

[0038] A method for preparing a lightweight composite porcelain clay, the method comprising the following preparation steps:

[0039] (1) mixing silicon carbide whiskers and 0.025 mol / L tris(hydroxymethylaminomethane) aqueous solution at a mass ratio of 1:2000, ultrasonically dispersing for 25 min, adding 2 g / L dopamine hydrochloride, stirring at 25° C. and 250 rpm for 16 h, filtering, washing with deionized water for 4 times, and drying at 65° C. for 9 h to obtain modified silicon carbide whiskers;

[0040] (2) 3-glycidylpropyl(dimethoxy)methylsilane, methyltriethoxysilane, dimethyldiethoxysilane, methyldiethoxysilane and tetrahydrofuran were mixed, stirred at 30°C and 250 rpm for 25 min, and a hydrochloric acid solution 5.5 times the mass of 3-glycidylpropyl(dimethoxy)methylsilane was added at a uniform rate within 7 min, and the mixture was stirred for 24 h. The mixture was heated to 55°C and stirred for 24 h. The mixture was rotary evaporated for 1.5 h. Ethyl acetate was added for extraction. The mixture was washed with a saturated sodium hydroxide solution for 4 times and dried with anhydrous calcium chloride for 24 h to obtain a silicone resin. The silicone resin, 2-propylene-1-boric acid, chloroplatinic acid and toluene were mixed in a mass ratio of 1:1.5:0.02:5, stirred at 70°C and 150 rpm for 15 min in a nitrogen atmosphere, heated to 110°C and stirred for 12 h. The mixture was rotary evaporated at 70°C for 1.5 h and cooled naturally to room temperature to obtain a modified silicone resin.

[0041] (3) Mix montmorillonite, polyethylene glycol and deionized water in a mass ratio of 1:0.065:65, and ultrasonically disperse at 25°C for 10 min. Heat to 85°C, add styrene (2.3 times the mass of montmorillonite), 4-vinylaniline (1 times the mass of montmorillonite), dibenzoyl peroxide (0.065 times the mass of montmorillonite) and divinylbenzene (0.4 times the mass of montmorillonite), stir for 1.5 h, heat to 95°C and continue stirring for 1 h. Cool naturally to room temperature and filter, wash with deionized water 4 times, and dry at 60°C for 24 h to obtain modified montmorillonite.

[0042] (4) The modified montmorillonite, modified silicone resin and ethanol solution were mixed in a mass ratio of 1:0.15:0.25, ultrasonically dispersed for 1.5 hours, and 0.055 times the mass of modified silicon carbide whiskers of the modified montmorillonite were added, stirred at 1000 rpm for 12 hours, and 0.15 times the mass of composite ceramic powder of the modified montmorillonite were added. The mixture was stirred and granulated with a disc granulator at 50 r / min, and dried at 85°C for 12 hours to obtain a green body; the green body was gradually heated and then naturally cooled to room temperature to obtain a lightweight composite porcelain clay.

[0043] Embodiment 3:

[0044] A method for preparing a lightweight composite porcelain clay, the method comprising the following preparation steps:

[0045] (1) Silicon carbide whiskers and 0.03 mol / L tris(hydroxymethyl)aminomethane) aqueous solution were mixed at a mass ratio of 1:2500, ultrasonically dispersed for 30 min, 3 g / L dopamine hydrochloride was added, stirred at 30° C. and 300 rpm for 15 h, filtered, washed with deionized water for 5 times, and dried at 70° C. for 8 h to obtain modified silicon carbide whiskers;

[0046] (2) 3-glycidylpropyl (dimethoxy)methylsilane, methyltriethoxysilane, dimethyldiethoxysilane, methyldiethoxysilane and tetrahydrofuran were mixed, stirred at 35°C and 300 rpm for 20 min, and a hydrochloric acid solution of 6 times the mass of 3-glycidylpropyl (dimethoxy)methylsilane was added at a uniform rate within 8 min, and the stirring was continued for 23 h. The mixture was heated to 60°C and stirred for 23 h. The mixture was rotary evaporated for 2 h. Ethyl acetate was added for extraction. The mixture was washed with saturated sodium hydroxide solution for 5 times and dried with anhydrous calcium chloride for 25 h to obtain a silicone resin. The silicone resin, 2-propylene-1-boric acid, chloroplatinic acid and toluene were mixed in a mass ratio of 1:2:0.03:6, stirred at 75°C and 200 rpm in a nitrogen atmosphere for 10 min, heated to 115°C and stirred for 11 h. The mixture was rotary evaporated at 75°C for 1 h and naturally cooled to room temperature to obtain a modified silicone resin.

[0047] (3) Mix montmorillonite, polyethylene glycol and deionized water in a mass ratio of 1:0.07:70, and ultrasonically disperse at 30°C for 15 min. Heat to 90°C, add styrene (2.4 times the mass of montmorillonite), 4-vinylaniline (1.5 times the mass of montmorillonite), dibenzoyl peroxide (0.07 times the mass of montmorillonite) and divinylbenzene (0.5 times the mass of montmorillonite), stir for 1 h, heat to 100°C and continue stirring for 0.9 h. Cool naturally to room temperature and filter, wash with deionized water 5 times, and dry at 65°C for 23 h to obtain modified montmorillonite.

[0048] (4) The modified montmorillonite, modified silicone resin and ethanol solution were mixed in a mass ratio of 1:0.2:0.3, ultrasonically dispersed for 2 hours, added with 0.06 times the mass of modified silicon carbide whiskers of the modified montmorillonite, stirred at 1100 rpm for 11 hours, added with 0.2 times the mass of composite ceramic powder of the modified montmorillonite, stirred and granulated with a disc granulator at 55 r / min, and dried at 90 ° C for 11 hours to obtain a green body; the green body was gradually heated and then naturally cooled to room temperature to obtain a lightweight composite porcelain clay.

[0049] Comparative Example 1:

[0050] A method for preparing a lightweight composite porcelain clay, the method comprising the following preparation steps:

[0051] (1) 3-glycidylpropyl(dimethoxy)methylsilane, methyltriethoxysilane, dimethyldiethoxysilane, methyldiethoxysilane and tetrahydrofuran were mixed, stirred at 30°C and 250 rpm for 25 min, a hydrochloric acid solution 5.5 times the mass of 3-glycidylpropyl(dimethoxy)methylsilane was added at a uniform rate within 7 min, stirring was continued for 24 h, the temperature was raised to 55°C and stirring was continued for 24 h, rotary evaporated for 1.5 h, ethyl acetate was added for extraction, washed with saturated sodium hydroxide solution 4 times, and dried with anhydrous calcium chloride for 24 h to obtain a silicone resin; silicone resin, 2-propylene-1-boric acid, chloroplatinic acid and toluene were mixed in a mass ratio of 1:1.5:0.02:5, stirred at 70°C and 150 rpm for 15 min in a nitrogen atmosphere, the temperature was raised to 110°C and stirring was continued for 12 h, rotary evaporated at 70°C for 1.5 h, and naturally cooled to room temperature to obtain a modified silicone resin;

[0052] (2) Mix montmorillonite, polyethylene glycol and deionized water in a mass ratio of 1:0.065:65, disperse them ultrasonically at 25°C for 10 min, heat them to 85°C, add styrene (2.3 times the mass of montmorillonite), 4-vinylaniline (1 times the mass of montmorillonite), dibenzoyl peroxide (0.065 times the mass of montmorillonite) and divinylbenzene (0.4 times the mass of montmorillonite), stir for 1.5 h, heat them to 95°C and continue stirring for 1 h, cool them naturally to room temperature, filter them, wash them with deionized water 4 times, and dry them at 60°C for 24 h to obtain modified montmorillonite;

[0053] (3) The modified montmorillonite, modified silicone resin and ethanol solution were mixed in a mass ratio of 1:0.15:0.25, ultrasonically dispersed for 1.5 hours, 0.055 times the mass of the modified montmorillonite silicon carbide whiskers were added, stirred at 1000 rpm for 12 hours, and 0.15 times the mass of the modified montmorillonite composite ceramic powder was added. The mixture was stirred and granulated with a disc granulator at 50 r / min, and dried at 85°C for 12 hours to obtain a green body; the green body was gradually heated and then naturally cooled to room temperature to obtain a lightweight composite porcelain clay.

[0054] Comparative Example 2:

[0055] A method for preparing a lightweight composite porcelain clay, the method comprising the following preparation steps:

[0056] (1) mixing silicon carbide whiskers and 0.025 mol / L tris(hydroxymethylaminomethane) aqueous solution at a mass ratio of 1:2000, ultrasonically dispersing for 25 min, adding 2 g / L dopamine hydrochloride, stirring at 25° C. and 250 rpm for 16 h, filtering, washing with deionized water for 4 times, and drying at 65° C. for 9 h to obtain modified silicon carbide whiskers;

[0057] (2) 3-glycidylpropyl(dimethoxy)methylsilane, methyltriethoxysilane, dimethyldiethoxysilane, methyldiethoxysilane and tetrahydrofuran were mixed, stirred at 30° C. and 250 rpm for 25 min, and a hydrochloric acid solution with a mass of 5.5 times that of 3-glycidylpropyl(dimethoxy)methylsilane was added at a uniform rate within 7 min, and the mixture was stirred for 24 h. The mixture was heated to 55° C. and stirred for 24 h. The mixture was rotary evaporated for 1.5 h, and ethyl acetate was added for extraction. The mixture was washed with a saturated sodium hydroxide solution for 4 times, and dried with anhydrous calcium chloride for 24 h to obtain a silicone resin.

[0058] (3) Mix montmorillonite, polyethylene glycol and deionized water in a mass ratio of 1:0.065:65, and ultrasonically disperse at 25°C for 10 min. Heat to 85°C, add styrene (2.3 times the mass of montmorillonite), 4-vinylaniline (1 times the mass of montmorillonite), dibenzoyl peroxide (0.065 times the mass of montmorillonite) and divinylbenzene (0.4 times the mass of montmorillonite), stir for 1.5 h, heat to 95°C and continue stirring for 1 h. Cool naturally to room temperature and filter, wash with deionized water 4 times, and dry at 60°C for 24 h to obtain modified montmorillonite.

[0059] (4) The modified montmorillonite, silicone resin and ethanol solution were mixed in a mass ratio of 1:0.15:0.25, ultrasonically dispersed for 1.5 hours, and modified silicon carbide whiskers (0.055 times the mass of the modified montmorillonite) were added, stirred at 1000 rpm for 12 hours, and composite ceramic powder (0.15 times the mass of the modified montmorillonite) was added. The mixture was stirred and granulated with a disc granulator at 50 r / min, and dried at 85°C for 12 hours to obtain a green body; the green body was gradually heated and then naturally cooled to room temperature to obtain a lightweight composite porcelain clay.

[0060] Comparative Example 3:

[0061] A method for preparing a lightweight composite porcelain clay, the method comprising the following preparation steps:

[0062] (1) mixing silicon carbide whiskers and 0.025 mol / L tris(hydroxymethylaminomethane) aqueous solution at a mass ratio of 1:2000, ultrasonically dispersing for 25 min, adding 2 g / L dopamine hydrochloride, stirring at 25° C. and 250 rpm for 16 h, filtering, washing with deionized water for 4 times, and drying at 65° C. for 9 h to obtain modified silicon carbide whiskers;

[0063] (2) 3-glycidylpropyl(dimethoxy)methylsilane, methyltriethoxysilane, dimethyldiethoxysilane, methyldiethoxysilane and tetrahydrofuran were mixed, stirred at 30°C and 250 rpm for 25 min, and a hydrochloric acid solution 5.5 times the mass of 3-glycidylpropyl(dimethoxy)methylsilane was added at a uniform rate within 7 min, and the mixture was stirred for 24 h. The mixture was heated to 55°C and stirred for 24 h. The mixture was rotary evaporated for 1.5 h. Ethyl acetate was added for extraction. The mixture was washed with a saturated sodium hydroxide solution for 4 times and dried with anhydrous calcium chloride for 24 h to obtain a silicone resin. The silicone resin, 2-propylene-1-boric acid, chloroplatinic acid and toluene were mixed in a mass ratio of 1:1.5:0.02:5, stirred at 70°C and 150 rpm for 15 min in a nitrogen atmosphere, heated to 110°C and stirred for 12 h. The mixture was rotary evaporated at 70°C for 1.5 h and cooled naturally to room temperature to obtain a modified silicone resin.

[0064] (3) Mix montmorillonite, modified silicone resin and ethanol solution in a mass ratio of 1:0.15:0.25, ultrasonically disperse for 1.5 hours, add modified silicon carbide whiskers (0.055 times the mass of montmorillonite), stir at 1000 rpm for 12 hours, add composite ceramic powder (0.15 times the mass of montmorillonite), stir and granulate with a disc granulator at 50 r / min, and dry at 85°C for 12 hours to obtain a green body; gradually heat the green body and then naturally cool it to room temperature to obtain a lightweight composite porcelain clay.

[0065] Test Case

[0066] 1. Plasticity

[0067] Test method: Take spherical samples of the same size from the green bodies obtained in each embodiment and the comparative example, and test the plasticity index according to the plasticity index method: plasticity index = (sample diameter - height when cracks appear) × load.

[0068] 2. Thermal insulation

[0069] Test method: Take the same samples of the lightweight composite porcelain clay obtained in each embodiment and the comparative example, and measure the thermal conductivity using a TC3000 thermal conductivity measuring instrument in accordance with GB / T11205.

[0070] 3. Crack resistance

[0071] Test method: Take samples of 2cm×2cm×2cm size from the lightweight composite porcelain clay obtained in each embodiment and the comparative example, and use a digital hydraulic pressure testing machine (YES-600) to measure the compressive strength of the samples at a pressure rate of 0.1kN / s.

[0072] Table 1 below shows the analysis results of the plasticity, thermal insulation and crack resistance of the lightweight composite porcelain clay of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3.

[0073] Table 1

[0074]

[0075] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the lightweight composite porcelain clay prepared by the present invention has good plasticity, heat preservation and crack resistance.

[0076] By comparison, Examples 1, 2, and 3 have a higher plasticity index and a lower thermal conductivity than Comparative Example 1, indicating that a layer of polydopamine is formed on the surface of the silicon carbide whisker, and the phenolic hydroxyl group can not only form a reversible crosslink with boric acid, but also form a covalent crosslink with the amino group and a coordination bond with the metal, thereby improving the plasticity of the lightweight composite porcelain clay; the carbonization of polydopamine during the sintering process can also produce pores, thereby improving the thermal insulation of the lightweight composite porcelain clay.

[0077] By comparison, Examples 1, 2, and 3 have higher plasticity index and compressive strength than Comparative Example 2, which illustrates that 2-propylene-1-boric acid is grafted by hydrosilylation to introduce a boric acid structure, forming a reversible borate ester cross-linking network at low temperature, and undergoing a carbon thermal reduction reaction with free carbon during high-temperature calcination to fill and support the pore structure, thereby improving the plasticity and crack resistance of the lightweight composite porcelain clay.

[0078] By comparison, Examples 1, 2, and 3 have a higher plasticity index and a lower thermal conductivity than Comparative Example 3, which illustrates that the synergistic pore formation by polyethylene glycol and styrene during high-temperature calcination improves the thermal insulation of the lightweight composite porcelain clay; at the same time, 4-vinylaniline participating in the surface polymerization introduces an amino group, which reacts with the epoxy group in the silicone resin at low temperatures to form a chemically bonded and high-temperature removable hydroxyl structure, further improving the plasticity and thermal insulation of the lightweight composite porcelain clay.

[0079] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a lightweight composite porcelain clay, characterized in that: The method comprises the following preparation steps: (1) reacting silicon carbide whiskers with a tris(hydroxymethyl)aminomethane aqueous solution to obtain modified silicon carbide whiskers; (2) reacting 3-glycidylpropyl(dimethoxy)methylsilane, methyltriethoxysilane, dimethyldiethoxysilane and methyldiethoxysilane to obtain a silicone resin; reacting the silicone resin with 2-propylene-1-boric acid to obtain a modified silicone resin; (3) mixing montmorillonite, polyethylene glycol, styrene, 4-vinylaniline and divinylbenzene to obtain modified montmorillonite; (4) The modified montmorillonite, modified silicone resin and composite ceramic powder are mixed and then sintered at a gradient temperature to obtain a lightweight composite porcelain clay.

2. The method for preparing a lightweight composite porcelain clay according to claim 1, characterized in that: The method comprises the following preparation steps: (1) mixing silicon carbide whiskers and 0.02-0.03 mol / L tris(hydroxymethyl)aminomethane) aqueous solution at a mass ratio of 1:(1500-2500), ultrasonically dispersing for 20-30 min, adding 1-3 g / L dopamine hydrochloride, stirring at 20-30° C. and 200-300 rpm for 15-17 h, filtering, washing with deionized water for 3-5 times, and drying at 60-70° C. for 8-10 h to obtain modified silicon carbide whiskers; (2) 3-glycidylpropyl(dimethoxy)methylsilane, methyltriethoxysilane, dimethyldiethoxysilane, methyldiethoxysilane and tetrahydrofuran were mixed and stirred at 25-35°C and 200-300 rpm for 20-30 min, and a hydrochloric acid solution of 5-6 times the mass of 3-glycidylpropyl(dimethoxy)methylsilane was added at a uniform rate within 6-8 min, and the stirring was continued for 23-25 ​​h. The temperature was raised to 50-60°C and the stirring was continued for 23-25 ​​h. The mixture was rotary evaporated for 1-2 h, and ethyl acetate was added for extraction. Wash with saturated sodium hydroxide solution for 3 to 5 times, dry with anhydrous calcium chloride for 23 to 25 hours to obtain silicone resin; mix silicone resin, 2-propylene-1-boric acid, chloroplatinic acid and toluene in a mass ratio of 1: (1 to 2): (0.01 to 0.03): (4 to 6), stir at 65 to 75° C. and 100 to 200 rpm for 10 to 20 minutes in a nitrogen atmosphere, heat to 105 to 115° C. and continue stirring for 11 to 13 hours, rotary evaporate at 65 to 75° C. for 1 to 2 hours, and naturally cool to room temperature to obtain modified silicone resin; (3) Mix montmorillonite, polyethylene glycol and deionized water in a mass ratio of 1:(0.06-0.07):(60-70), perform ultrasonic dispersion at 20-30°C for 5-15 min, heat to 80-90°C, add styrene (2.2-2.4 times the mass of montmorillonite), 4-vinylaniline (0.5-1.5 times the mass of montmorillonite), dibenzoyl peroxide (0.06-0.07 times the mass of montmorillonite) and divinylbenzene (0.3-0.5 times the mass of montmorillonite), stir for 1-2 h, heat to 90-100°C and continue stirring for 0.9-1.1 h, cool naturally to room temperature, filter, wash with deionized water 3-5 times, and dry at 55-65°C for 23-25 ​​h to obtain modified montmorillonite; (4) The modified montmorillonite, modified silicone resin and ethanol solution are mixed in a mass ratio of 1: (0.1-0.2): (0.2-0.3), and ultrasonically dispersed for 1-2 hours, and 0.05-0.06 times the mass of the modified montmorillonite modified silicon carbide whiskers are added, and stirred at 900-1100 rpm for 11-13 hours, and 0.1-0.2 times the mass of the modified montmorillonite composite ceramic powder is added, and granulated by a disc granulator at 45-55 r / min, and dried at 80-90°C for 11-13 hours to obtain a green body; the green body is gradually heated and then naturally cooled to room temperature to obtain a lightweight composite porcelain clay.

3. The method for preparing a lightweight composite porcelain clay according to claim 2, characterized in that: In step (2), 3-glycidylpropyl(dimethoxy)methylsilane, methyltriethoxysilane, dimethyldiethoxysilane, methyldiethoxysilane and tetrahydrofuran are mixed in a mass ratio of 1:2:0.7:0.8:

19.

4. The method for preparing a lightweight composite porcelain clay according to claim 2, characterized in that: The pH of the hydrochloric acid solution in step (2) is 1.

5. The method for preparing a lightweight composite porcelain clay according to claim 2, characterized in that: The volume fraction of the ethanol solution in step (4) is 50%.

6. The method for preparing a lightweight composite porcelain clay according to claim 2, characterized in that: The composite ceramic powder in step (4) is obtained by mixing potassium feldspar powder and white gangue powder in a mass ratio of 1:0.3 and milling them with corundum balls on a planetary ball mill for 4 hours.

7. The method for preparing a lightweight composite porcelain clay according to claim 2, characterized in that: The gradient heating in step (4) is to heat to 400°C at a rate of 5°C / min for preheating for 60 minutes, heat to 1000°C at a rate of 4°C / min, keep warm for 2 hours, and then heat to 1450°C at a rate of 2°C / min, and keep warm for 4 hours.

Citation Information

Patent Citations

  • Silicon carbide crystal whisker in-situ composite lithium ceramic material and preparation method thereof

    CN110590334A

  • Preparation method of high-temperature-resistant heat-insulating composite material

    CN111807808A

  • Preparation method of high-performance ceramic thermal insulation material and prepared material

    CN115073138A

  • Heat-insulating anticorrosive coating for pipelines and preparation method of heat-insulating anticorrosive coating

    CN117511401A

  • High-plasticity composite porcelain clay material with jade effect, preparation process and application of high-plasticity composite porcelain clay material in porcelain products

    CN117843356A